Generativity, comparative grammar, and the syntax vs. the lexicon debates - Gillian Catriona Ramchand (Nordlyd: Tromsø University Working Papers on Language & Linguistics)
Within linguistic theory, the division of labour between syntax and the lexicon has been a central issue for debate among different architectures of grammar, roughly corresponding to the distinction between memorization and rule governed aspects of language competence. In this article, I give some historical context for these debates, concluding that differences in architectural assumptions are only resolvable ultimately if we are willing to allow these implementational decisions to have consequences for (and make predictions concerning) human behaviours or mental processes. I proceed then to assess the psycholinguistic evidence concerning the lexicon and processing from the cognitive science literature, and offer a reassessment of what this means for the linguistic debates that have dominated discussions of the lexicon to this date. My conclusion will be that some of the comfortable dichotomies often relied on in these discussions are untenable and that some of the classical positions need to be reevaluated.